QTL-Seq Analysis for Identification of Resistance Loci to Bacterial Canker in Tomato - Abebe, Alebel Mekuriaw; Oh, Chang-Sik; Kim, Hyoung Tae; Choi, Giwon; Seo, Eunyoung; Yeam, Inhwa; Lee, Je Min (Frontiers in Plant Science, 2022)
Bacterial canker caused by Clavibacter michiganensis (Cm) is one of the most economically important vascular diseases causing unilateral leaf wilting, stem canker, a bird’s-eye lesion on fruit, and whole plant wilting in tomato. There is no commercially available cultivar with bacterial canker resistance, and genomics-assisted breeding can accelerate the development of cultivars with enhanced resistance. Solanum lycopersicum ‘Hawaii 7998’ was found to show bacterial canker resistance. A QTL-seq was performed to identify the resistance loci using 909 F2 individuals derived from a cross between S. lycopersicum ‘E6203’ (susceptible) and ‘Hawaii 7998’, and a genomic region (37.24–41.15 Mb) associated with bacterial canker resistance on chromosome 6 (Rcm6) was found. To dissect the Rcm6 region, twelve markers were developed and several markers were associated with the resistance phenotypes. Among the markers, the Rcm6-9 genotype completely matched with the phenotype in the 47 cultivars. To further validate the Rcm6 as a resistance locus and the Rcm6-9 efficiency, subsequent analysis using F2 and F3 progenies was conducted. The progeny individuals with homozygous resistance allele at the Rcm6-9 showed significantly lower disease severity than those possessing homozygous susceptibility alleles. Genomes of five susceptible and two resistant cultivars were analyzed and previously known R-genes were selected to find candidate genes for Rcm6. Nucleotide-binding leucine-rich repeat, receptor-like kinase, and receptor-like protein were identified to have putative functional mutations and show differential expression upon the Cm infection. The DNA markers and candidate genes will facilitate marker-assisted breeding and provide genetic insight of bacterial canker resistance in tomato.